Hydrogen and humidity sensing based on WGMs of elastic polymer optical microresonators - (:unkn) unknown (Electromagnetics Academy, 2015)
We report hydrogen and humidity sensor employing elastic polymer (SU-8) optical microresonators. The sensing mechanism relies on the optical whispering gallery mode (WGM) resonance shifts in the transmission spectra of these microresonators. WGMs are excited through SU-8 waveguides in which a tunable laser light is coupled from an optical fiber. Relative humidity between 0 and 65% is detected at room temperature. For hydrogen sensing, the microresonators are coated with a thin layer of palladium (Pd) metal layer to increase the sensing performance. Hydrogen gas is detected reversibly between 0.3 and 1.5%. Hydrogen gas concentrations higher than 1.5% result irreversible degradation of the devices because of a phase transition occurring in the Pd layer.